Co-occurrence of GATA2 deficiency and probable constitutional mosaic STAG2 alteration in a young adult with myelodysplastic syndrome: a case report - Onda-Tabita Calugaru; Daniel Coriu; Cerasela Jardan; Claudia Tarniceriu; Daniela Cristina Anghel; Iulia Ursuleac (Frontiers in Medicine, 2026)
Germline predisposition syndromes are increasingly recognized in young patients presenting with myelodysplastic syndromes (MDS) and bone marrow failure. Among these, GATA2 deficiency represents a well-established cause of hereditary susceptibility to myeloid malignancies, whereas constitutional STAG2 alterations are rare and mainly associated with cohesinopathies and neurodevelopmental disorders. We report the case of a 25-year-old male presenting with hypocellular MDS, recurrent severe infections, lymphedema, cytopenias, psoriasis, and multiple dysmorphic features. The patient had previously received a clinical diagnosis of Emberger syndrome without molecular confirmation. Targeted next-generation sequencing identified pathogenic truncating variants in GATA2, STAG2, and ASXL1. The variant allele frequencies observed for GATA2 and STAG2, together with the patient's young age and syndromic phenotype, prompted additional testing using non-hematopoietic tissue. Analysis of buccal-derived DNA confirmed the germline GATA2 pathogenic variant and detected the STAG2 alteration at a variant allele frequency consistent with probable constitutional mosaicism. Cytogenetic studies excluded sex chromosome aneuploidy. The co-occurrence of GATA2 deficiency and probable constitutional mosaic STAG2 involvement raises the hypothesis that alterations affecting distinct hematopoietic regulatory mechanisms may contribute to the complex clinical phenotype; however, functional interaction between these alterations remains unproven. This case highlights the importance of comprehensive molecular evaluation and germline confirmation in young patients with MDS, particularly when clinical features suggest an underlying inherited predisposition or an atypical overlapping phenotype. It further illustrates the diagnostic challenge of distinguishing acquired from constitutional alterations and the importance of tissue-specific molecular assessment when constitutional mosaicism is suspected.